5-Hydroxymethylfurfural from fructose: an efficient continuous process in a water-dimethyl carbonate biphasic system with high yield product recovery. Issue 16 (28th July 2020) - Sayed, Mahmoud; Warlin, Niklas; Hulteberg, Christian; Munslow, Ian; Lundmark, Stefan; Pajalic, Oleg; Tunå, Per; Zhang, Baozhong; Pyo, Sang-Hyun; Hatti-Kaul, Rajni
Abstract : A facile, rapid process for 5-HMF production at high yield and purity using a green biphasic system. Abstract : Bio-based 5-hydroxymethylfurfural (5-HMF) and its derivatives have attracted enormous attention due to their valuable market potential. Production of pure 5-HMF is challenging owing to the high reactivity of its functional groups and formation of by-products. In this study, an efficient continuous process for 5-HMF production in a biphasic system and its recovery at high yield and selectivity was developed. After an initial screening of different solvents, a water/dimethyl carbonate (DMC) system was selected for acid catalyzed fructose dehydration in a continuous mode using 0.23 M HCl as a catalyst. Effects of various reaction parameters on substrate conversion, product yield and selectivity, were determined. The process using 30% (w/v) fructose in water with three times the volume of DMC at 1 min residence time in a tube reactor at 200 °C provided 96.5% fructose conversion and 87.2% 5-HMF yield with a selectivity of 85.5% and 95.8% in aqueous and organic phases, respectively. Increasing the fructose concentration in the water phase to 52% gave 96.4% conversion and 74% 5-HMF yield. Using a fructose-glucose mixture as substrate had no effect on fructose conversion but affected slightly the selectivity of 5-HMF in the aqueous phase. Recovery of 5-HMF with ≥93% purity from DMC was achieved by solvent evaporation under vacuum, and improved by prior treatment with activated carbon, especially together with Na2 CO3 . Evaluation of the purified 5-HMF in a reaction with pentaerythritol showed comparable performance to the commercial 5-HMF in the production of a spirocyclic diol, a monomer for the production of polyesters and polyurethane.